The requirements of nucleic acid test for COVID-19 during public health emergency: Current regulatory in Taiwan, Singapore, and the United States. Issue 11 (2nd November 2022) - Fan, Yin-Ting; Lee, Jin-Yu; Cheng, Yu-Che; Lin, Hsin-Hui; Chien, Chia-Hung; Tu, Pei-Weng; Chung, Hui-Wen
Abstract : In mid-2022, the COVID-19 cases have reached close to 562 million, but its overall infection rate is hard to confirm. Even with effective vaccines, break-through infections with new variants occur, and safe and reliable testing still plays a critical role in isolation of infected individuals and in control of an outbreak of a COVID-19 pandemic. In response to this urgent need, the diagnostic tests for COVID-19 are rapidly evolving and improving these days. The health authorities of many countries issued requirements for detecting SARS-CoV-2 diagnosis tests during the pandemic and have timely access to these tests to ensure safety and effectiveness. In this study, we compared the requirements of EUA in Taiwan, Singapore, and the United States. For the performance evaluations of nucleic acid extraction, inclusivity, limit of detection (LoD), cross-reactivity, interference, cutoff, and stability, the requirements are similar in the three countries. The use of natural clinical specimens is needed for clinical evaluation in Taiwan and the United States. However, carry-over and cross-contamination studies can be exempted in Taiwan and the United States but are required in Singapore. This review outlines requirements and insight to guide the test developers on the development of IVDs. Considering the rapidly evolving viruses and severe pandemic of COVID-19, timely and accurate diagnostic testing is imperative to the management of diseases. As noted above, the performance requirements for SARS-CoV-2 nucleic acid tests are similar between Taiwan, Singapore and the United States. The differences are mainly in two points: the recommended microorganisms for cross-reactivity study, and the specimen requirement for clinical evaluation. This study provides an overview of current requirements of SARS-CoV-2 nucleic acid tests in Taiwan, Singapore, and the United States.